A Geophysical Perspective on the Bulk Composition of Mars. Issue 2 (26th February 2018) - Khan, A.; Liebske, C.; Rozel, A.; Rivoldini, A.; Nimmo, F.; Connolly, J. A. D.; Plesa, A.‐C.; Giardini, D.
Abstract: We invert the Martian tidal response and mean mass and moment of inertia for chemical composition, thermal state, and interior structure. The inversion combines phase equilibrium computations with a laboratory‐based viscoelastic dissipation model. The rheological model, which is based on measurements of anhydrous and melt‐free olivine, is both temperature and grain size sensitive and imposes strong constraints on interior structure. The bottom of the lithosphere, defined as the location where the conductive geotherm meets the mantle adiabat, occurs deep within the upper mantle (∼200–400 km depth) resulting in apparent upper mantle low‐velocity zones. Assuming an Fe‐FeS core, our results indicate (1) a mantle with a Mg# (molar Mg/Mg+Fe) of ∼0.75 in agreement with earlier geochemical estimates based on analysis of Martian meteorites; (2) absence of bridgmanite‐ and ferropericlase‐dominated basal layer; (3) core compositions (15–18.5 wt% S), core radii (1, 730–1, 840 km), and core‐mantle boundary temperatures (1620–1690°C) that, together with the eutectic‐like core compositions, suggest that the core is liquid; and (4) bulk Martian compositions with a Fe/Si (weight ratio) of 1.66–1.81. We show that the inversion results can be used in tandem with geodynamic simulations to identify plausible geodynamic scenarios and parameters. Specifically, we find that the inversion results are largely reproducible by stagnant lid convection models for a range of initial viscosities (∼10 18 –10 20  Pa s) and radioactive element partitioning between crust and mantle around 0.01–0.1. The geodynamic models predict a mean surface heat flow between 15 and 25 mW/m 2 . Key Points: We constrain the bulk composition of Mars using geophysical data to an Fe/Si (wt) of 1.61 =− 1.67 and a molar Mg# of 0.745–0.751 The results indicate a large liquid core (1, 640–1, 740 km in radius) containing 13.5–16 wt% S and excludes a transition to a lower mantle We use the inversion results in tandem with geodynamic simulations to identify plausible geodynamic scenarios and parameters